Rapid quantitative analysis of double-stranded plasmid DNA with capillary gel electrophoresis for applications in quality control and radiation research - Marc Benjamin Hahn (Scientific Reports)
Abstract The quantification of different structures, isoforms and types of damage in plasmid DNA is of importance for applications in radiation research, DNA based bio-dosimetry, and pharmaceutical applications such as vaccine development. The standard method for quantitative analysis of plasmid DNA damage such as single-strand breaks (SSB), double-strand breaks (DSB) or various types of base-damage is Agarose gel electrophoresis (AGE). Despite being well established, AGE has various drawbacks in terms of time consuming handling and analysis procedures. A more modern, faster, cheaper and more reliable method is capillary gel electrophoresis (CGE). However, to establish this method in biotechnology, radiation-research and related fields, certain criteria in terms of accuracy, repeatability and linearity have to be tested and protocols have to be established. This study performs the relevant tests with a common model plasmid (pUC19, double-stranded DNA with 2686 basepairs) to establish a CGE based methodology for quantitative analysis with readily available commercial CGE systems. The advantages and limitations of the methods are evaluated and discussed, and the range of applicability is presented. As a further example, the kinetics of enzyme digestion of plasmid DNA by capillary gel electrophoresis was studied. The results of the study show for a model system consisting out of pUC19, the suitability of CGE for the quantification of different types of DNA damage and the related isoforms, such as supercoiled, open-circular and linear plasmid DNA.